Parents Perceptions and Attitudes Towards Sex Education at Kindergarten ABA Sudagaran. - Salsabila, Adnecha Attha; R Agustinus Arum Eka Nugroho (Universitas Negeri Semarang, 2025)
Cases of sexual abuse against children in Indonesia continue to increase, this has encouraged variouselements of society to be actively involved in providing sexual education. This research analyzes parents perceptionsand attitudes towards early childhood sex education. This type of research is quantitative research. The researchrespondents were all parents of Kindergarten ABA Sudagaran, totaling 80 people. The analytical method used ismultiple linear regression with IBM SPSS 26 software. The research results show that perception has an influence onsex education with a significance value of 0.000 < 0.05 and a calculated t value of 4.723 > t table 1.994. Then, attitudedoes not have a positive influence on sex education with a significance value of 0.152 > 0.05 and a calculated t valueof 1.447 < t table 1.994. The results of this study show that there is an influence between parents' perceptions of early childhood sexual education. Meanwhile, attitudes do not have a significant effect on early childhood sexualeducation. Parents believe that sexual education is important in protecting children from sexual violence. However,there are obstacles felt by parents in its implementation. As a follow-up, it is important to build communicationbetween teachers and parents to create harmonious understanding and beliefs regarding sexual education.